Mechanism of Permeability Evolution for Reservoir Sandstone with Different Physical Properties - Xianshan Liu; Ming Xu; Ke Wang (Geofluids)
Permeability of sandstones with different properties taken from Chongqing reservoirs has been measured and deeply discussed under increasing deviatoric stress. Corresponding to the distinct features in the stress-strain behaviors, the permeability of sandstones is found to evolve with a clear permeability decrease in the initial closure region, a constant permeability value in the elastic region, a permeability increase in the crack initiation and propagation region, a sharp permeability increase in the crack growth region, and a decrease permeability in the residual stage. The results also show that the variation patterns of permeability are similar for two reservoir sandstones under combination of confining pressure and water pressure; however, the strength and permeability are smaller for the sandstone with mud than that without mud, deeply indicating that mud-like materials have a relatively great impact on the mechanical properties and permeability, so mud components cannot be ignored for prediction of reservoir permeability. Furthermore, a statistical damage constitutive model considering hydraulic-mechanical coupling process is presented to calculate the damage variable D, illustrating that larger water pressure will result in a relatively smaller damage variables D and corresponding maximum, which explains that the permeability increases more rapidly and is larger for the sandstone without mud than that with mud, and sandstone damage related to corresponding circumferential crack strain and permeability has been investigated, also implying the evolution mechanism of permeability for two sandstones with different physical properties. Therefore, it is worth pointing out that rock physical properties have a great influence on the reservoir permeability under complex extraction conditions and cannot be ignored, which is necessary to improve the recovery ratio and productivity.